Vaccination Status and Influencing Factors of Delayed Vaccination in Toddlers Born to Hepatitis B Surface Antigen-Positive Mothers - Jinling Gao; Lin Luan; Yiheng Zhu; Jie Zhu; Zhiyuan Zhu; Tian Gong; Juan Xu; Na Liu (Vaccines)
Background: This study aims to analyze the vaccination status and factors influencing delayed vaccination among toddlers born to hepatitis B surface antigen (HBsAg)-positive mothers. Methods: Data of HBsAg-positive mothers between 1 January 2021 and 31 December 2022 were provided by the Suzhou Maternal and Child Health Care and Family Planning Service Center. The vaccination records were obtained from the Jiangsu Province Immunization Service Management Information System. Logistic regression analysis was used to analyze influencing factors of delayed vaccination. Results: A total of 4250 toddlers born to HBsAg-positive mothers were documented. The data revealed that the first dose of the hepatitis B vaccine was administered to 100% of the toddlers. In addition, the coverage of the National Immunization Program (NIP) vaccines among these toddlers ranged from 92.9% to 99.4%. The proportion of delayed NIP vaccination varied between 0% and 12.2%. The proportion of delayed Bacillus Calmette–Guérin (BCG) vaccination was 11.3%, with the delay predominantly observed between 4 and 6 months. Notably, the proportion of delayed BCG vaccination among the toddlers born to HBsAg-positive mothers was significantly higher than that in the general population. Additionally, the proportion of the first dose of non-NIP vaccines was 3.3–36.4%, and the proportion of DTaP-IPV/Hib was 27.0%. Logistic regression analysis revealed that the regional level, the mother’s human papillomavirus (HPV) vaccination status, and the infant’s birth weight were significant factors influencing the timeliness of vaccination. Conclusions: Although the vaccination status of toddlers born to HBsAg-positive mothers in Suzhou city remains stable, the issue of delayed vaccination requires attention. It is essential to continue strengthening targeted vaccine education to reduce vaccine hesitancy and improve the rate of timely vaccination.